Carbon stock and dynamics under improved tropical pasture and silvopastoral systems in Colombia Amazonia - Mosquera V., Octavio; Buurman, Peter; Ramírez, Bertha L.; Amézquita, María Cristina (Elsevier, 2012)
To evaluate the effect of land use change on soil organic carbon, the carbon contents and stocks of primary forest, degraded pasture, and four improved pasture systems in Colombian Amazonia were compared in a flat and a sloping landscape. The improved pastures were Brachiaria humidicola, and Brachiaria decumbens, either in monoculture or in combination with native legumes. The age of the treatments was 30 years for degraded pasture and 10 or 15 years for each of the improved pastures. Carbon fractions were Total C, Oxidizable C, and Non-Oxidizable (stable) C. Stocks were compared using a fixed soil mass base. The degraded pasture in the flat landscape was abandoned and dominated by weeds, while that in the sloping area was overgrazed. The latter had much lower C stocks than the former. B. humidicola monoculture had the highest stocks both in flat and sloping areas, while the effect of the other three treatments varied. C replacement based on δ13C indicated that after 30 years, the degraded pasture still contained more than 50% forest-derived C in its topsoil. The fraction in the topsoil that is not replaced roughly coincides with the Stable C fraction. δ13C values suggest that the changes in carbon stocks ascribed to differences in land use may be at least partially inherited from the previous land use, thus confusing the interpretation of land use effects. Nevertheless, the introduction of improved pastures on degraded grassland is a feasible alternative of land use both for carbon sequestration and as an attractive economic alternative to farmers.